Energy e-commerce user portrait and multi-agent cooperative game price mechanism design - Yang, Biao; Liu, Suwei; Gao, Hongda (Frontiers in Energy Research, 2024)
With the development of the big data, our lives have gradually entered the information age, which has changed and reshaped the behavior of enterprises and consumers. In this paper, a user portrait clustering model based on big data is proposed to implement business model design for specific groups after clustering, target potential user groups for active marketing, and promote actual purchase behavior. In this paper, cost factor, risk factor and contribution factor are introduced to improve the basic cooperative game allocation method. The improved model considers the operating cost of the main body, the level of risk and the contribution proportion of actual energy supply respectively. In order to verify the effectiveness and applicability of the benefit distribution strategy based on cooperative game proposed by the project. The research results provide a certain reference for precision marketing of relevant industries and enterprises.